2024
DOI: 10.1590/1984-0462/2024/42/2022173
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron deficiency anemia and sleep duration in the first year of life

Abstract: Objective: The aim of this study was to investigate the association between iron deficiency anemia and sleep duration in the first year of life. Methods: A total of 123 infants were investigated, with sleep being evaluated at 3, 6, and 12 months of age and anemia at birth and 6 months. The cutoff points for anemia and short sleep duration were hemoglobin <11 g/dL (at birth and/or 6 months) and <10 h (at 3, 6, and 12 months), respectively. The comparison of the average sleep time between infants with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The article by Rodrigues Junior et al addresses two frequent and important aspects that are often neglected in infant health care: iron deficiency anemia and sleep hygiene. 1 The study revealed that children with anemia were more likely to have short sleep duration, demonstrating that the concomitance of these factors can compromise the development of the central nervous system.…”
mentioning
confidence: 94%
“…The article by Rodrigues Junior et al addresses two frequent and important aspects that are often neglected in infant health care: iron deficiency anemia and sleep hygiene. 1 The study revealed that children with anemia were more likely to have short sleep duration, demonstrating that the concomitance of these factors can compromise the development of the central nervous system.…”
mentioning
confidence: 94%